Cytomegalovirus retinitis treated with valganciclovir in Wegener’s granulomatosis - Kabata Y (Dove Medical Press, 2012)
Yoshiaki Kabata1, Genichiro Takahashi1, Hiroshi Tsuneoka21Department of Ophthalmology, Jikei University School of Medicine, Katsushika Medical Center, Katsushika, Tokyo, Japan; 2Department of Ophthalmology, Jikei University School of Medicine, Minato, Tokyo, JapanAbstract: A case of cytomegalovirus (CMV) retinitis in a patient with Wegener’s granulomatosis treated with oral valganciclovir as maintenance therapy is reported. A 68-year-old male patient with anti-proteinase-3 ANCA-positive Wegener’s granulomatosis who was receiving immunosuppressive therapy with methylprednisolone, cyclophosphamide, and azathioprine developed CMV retinitis. The patient received intravenous ganciclovir as induction therapy and oral valganciclovir as maintenance therapy. The patient responded to treatment and showed no recurrence for 8 months. There were no serious adverse effects associated with oral valganciclovir. Oral valganciclovir is convenient and effective for the management of CMV retinitis in the patient with Wegener’s granulomatosis.Keywords: cytomegalovirus retinitis, Wegener’s granulomatosis, valganciclovir, ganciclovir, maintenance therapy